Integrative Rehabilitation for War-Related Polytrauma: A Narrative Review of Multidimensional Strategies and Implementation Challenges - Ji Sun; Y. M. R. C. Hirushan; Harith Randula; Weixin Zhang; Qianhao Wu; Jia Han (Healthcare, 2026)
Objective: Modern high-intensity warfare, such as the Russo-Ukrainian conflict, generates a high incidence of multisystem polytrauma, blast-induced traumatic brain injury, and limb amputations often complicated by post-traumatic stress disorder and chronic pain. Traditional specialised rehabilitation protocols are structurally inadequate for these co-occurring symptoms and rely heavily on medical treatments, increasing the risk of opioid dependency. The primary aim of this review is to conceptualise a multidimensional integrative framework for war-related polytrauma; a secondary aim is to evaluate and summarise the evidence underpinning its key rehabilitation strategies for limited-resource, post-conflict environments. Methods: This narrative review synthesises evidence identified through targeted database searches and purposive selection guided by clinical relevance, methodological quality, and applicability to war-related polytrauma across physical, technological, and non-pharmacological rehabilitation domains. Evidence was evaluated using a four-tier (A–D) hierarchy, comprising Tier A (systematic reviews and RCTs), Tier B (prospective cohort studies and non-randomised controlled trials), Tier C (descriptive, case-series, and retrospective studies), and Tier D (exploratory, mechanism-based, or expert opinion evidence). No systematic inclusion/exclusion protocol was applied, and no claims of comprehensive search coverage are made. Results: Concurrent physical and trauma-focused psychological rehabilitation, evidenced by reduced pain and psychological symptom burden alongside improved functional independence, is supported by high-quality evidence (Tier A) for managing comorbid polytrauma. Robotic exoskeletons and AI-supported tele-rehabilitation demonstrate dose-dependent motor benefits in selected rehabilitation populations (Tier A–B), but their scalability in wartime settings is contingent on electricity supply, connectivity, equipment maintenance, and trained personnel. Acupuncture shows Tier A evidence for neuropathic pain and Tier B cost-effectiveness; evidence for phantom limb pain and PTSD is preliminary (Tier C–D) and requires dedicated RCTs in veteran populations. Ayurvedic herbal interventions are exploratory (Tier C–D) with no war-specific clinical trials; mechanistic plausibility is discussed as hypothesis-generating only. Conclusions: Addressing the war-related rehabilitation gap requires integration of biomedical care, technology-assisted rehabilitation, and evidence-graded non-pharmacological adjuncts within a structured biopsychosocial framework. Future priorities include pragmatic, adapted trial designs (e.g., stepped-wedge or cohort-embedded designs, which are more feasible than classical RCTs under wartime conditions) for acupuncture in phantom limb pain, feasibility trials for robotic rehabilitation in frontline-adjacent facilities, and health-economic modelling adapted to the Ukrainian context.